A clinical study to assess the gingivitis reduction efficacy of a novel stannous-containing fluoride dentifrice - Xu, Zhipeng; He, Tao; He, Yanyan; Fei, Phil; Sun, Lily; Chen, Yamei; Li, Jiahui (American journal of dentistry, 2021)
To assess the gingivitis reduction efficacy of a novel stannous-containing fluoride dentifrice relative to a negative control. 100 generally healthy adults with 10 or more gingival bleeding sites based on the Mazza Modification of the Papillary Bleeding Index (Mazza GI) were enrolled into a 2-week randomized, controlled, double-blind, single-center, two-treatment, parallel group clinical study. The subjects were randomly assigned to the stannous-containing dentifrice group (experimental group) or the sodium fluoride dentifrice group (negative control group). An oral examination and Mazza GI examination were conducted at Baseline, Day 3 and Week 2 post-baseline by a qualified dental examiner. 98 subjects completed the study. The experimental group provided a significant reduction in Mazza GI scores and number of bleeding sites relative to baseline at Day 3 and Week 2 (P< 0.0001). The negative control did not provide significant reductions versus baseline for either measure at either timepoint (P> 0.3). At Day 3, the experimental group provided a statistically significant reduction of Mazza GI scores and number of bleeding sites compared with the negative control group (P< 0.0001). At Week 2, the experimental group showed 24.11% lower Mazza GI scores and 54.81% fewer bleeding sites than the negative control group (P< 0.0001). The results demonstrated that the novel stannous-containing fluoride dentifrice had a superior anti-gingivitis effect compared to the sodium fluoride negative control dentifrice, which was evident as quickly as 3 days after use and further improved after 2 weeks of usage.